Validation of analytical method for determination of terbuthylazine and S-metolachlor residues in soil - Lazić Sanja (Proceedings of the International Symposium on Analytical and Environmental Problems, 2017)
Terbuthylazine and s-metolachlor are commonly used herbicides, especially after prohibition of some other triazine and chloracetanilide herbicides. However, often used pesticides pose the risk of soil contamination due to their persistence, toxicity and bioaccumulation. The trace determination of herbicide residues, generally in environmental samples, presents a challenging analytical problem. The present work was carried out to analyze terbuthylazine and s-metolachlor residues in soil based on high performance liquid chromatography (HPLC), and QuEChERS extraction method. The method was optimized and validated according to the parameters of precision, accuracy, linearity, limits of detection and limits of quantification. Analysis was carried out using an HPLC-UV diode array detection system (Agilent 1100, USA), with an Agilent Zorbax Eclipse C18 column (50 mm × 4.6 mm, 1.8 μm) and mobile phase consisting of ultrapure water and acetonitrile (55/45, v/v). Mean recoveries obtained from soil samples fortified at three different levels ranged from 81 to 92%. The method detection limits ranged from 0.01 to 0.05 mg kg-1 . Obtained results completely fulfilled the SANCO/825/00 rev. 8.1 16/11/2010 criteria.